Search Engine Optimization Tool With Web Crawler, Page Density Checker, Search Density Checker, and Similar Page Checker - Körpe, Yiğitalp (MEF Üniversitesi Fen Bilimleri Enstitüsü, 2021)
For this project, I built an SEO tool. I am working in digital marketing, and we are using various tools, and services frequently. But due to budget constraints or a variety of tools, we cannot reach each tool all the time. Even these tools are not easy to reach, some of their features are fundamental for jobs we are handling every day. Therefore, we needed to find their free / less expensive versions or use them within their free limits. But since I learned some coding and saw programming possibilities, I see that some must-have features are not that hard to code or complicated. Therefore, I created a small program to help my career and my budget. This script helps generally SEO reporting.This script has 4 main features. Web crawler feature can crawl the website and provide website’s page details. Page density checker feature can report the word density of the page. Search density checker searches the input query on Google, reports top 10 results and their word density. Finally similar page checker crawls the website and runs cosine similarity test for each page of the website.
İnternet sitesi tarayıcısı, sayfa yoğunluk, arama yoğunluk kontrollü ve benzer sayfa denetleyicisi ile arama motoru optimizasyon aracı
Keywords: SEO, Web Crawler, Page Crawling, Content Creation, Digital Marketing